Weather - Steele, Philip; Moran, Mike (Essex Miles Kelly Publishing Ltd, 2020)
This humorous twist on the perennially popular Q & A format takes a sideways look at all that is wild and wonderful about the weather. Quirkily illustrated characters and playful text reveal the amazing answers. Find out how clouds make lightning, which plants need the wind, and why Arctic foxes get a new look in winter
Science (Nature)
Keywords: Biology